2000
DOI: 10.1073/pnas.97.1.394
|View full text |Cite
|
Sign up to set email alerts
|

The Nef protein of HIV-1 associates with rafts and primes T cells for activation

Abstract: The Nef protein is an important virulence factor of primate lentiviruses, yet the mechanisms by which it exerts this influence are imperfectly understood. Here, using an inducible system, we demonstrate that Nef increases IL-2 secretion from T cells stimulated via CD3 or CD28. This effect requires the conservation of the Nef myristoylation signal and SH3-binding proline-based motif. Together with several proteins involved in the initiation and propagation of T cell signaling, Nef associates with membrane micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
202
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(221 citation statements)
references
References 58 publications
16
202
3
Order By: Relevance
“…Also, some previous reports have shown increased in vitro T-cell activation (16,40,60) (enhanced expression of CD69 and CD25 [3] and IL-2 production [52,54,55,67,70]) in HIV-1 or SIV (1, 15, 37) Nefexpressing CD4 ϩ T cells (reviewed in references 25 and 51). However, other results showed that Nef did not affect CD69 or CD25 expression (9,30,54,56,67) and was in fact blocking proximal signal required for CD69 expression (30) and inhibiting activation pathways (2,11,20,21) in vitro. These contrasting in vitro results most likely reflect the T cells used for experimentation by different groups and may not be comparable to the data obtained here with the Tg CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, some previous reports have shown increased in vitro T-cell activation (16,40,60) (enhanced expression of CD69 and CD25 [3] and IL-2 production [52,54,55,67,70]) in HIV-1 or SIV (1, 15, 37) Nefexpressing CD4 ϩ T cells (reviewed in references 25 and 51). However, other results showed that Nef did not affect CD69 or CD25 expression (9,30,54,56,67) and was in fact blocking proximal signal required for CD69 expression (30) and inhibiting activation pathways (2,11,20,21) in vitro. These contrasting in vitro results most likely reflect the T cells used for experimentation by different groups and may not be comparable to the data obtained here with the Tg CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on numerous observations, Nef appears to play a multifaceted role; it was found to promote high virulence and accelerate viral replication (reviewed in reference 26) and to downregulate cell surface CD4 (47,61) and major histocompatibility complex class I (MHC-I) (35) molecules, as well as to affect T-cell activation (1,3,15,38,62), proliferation (12,36), and cytokine (interleukin-2 [IL-2] and IL-10) production (7,38,67). However, numerous controversial findings have been reported.…”
mentioning
confidence: 99%
“…Myristoylation is essential for almost all the functions ascribed to Nef, including membrane localization within lipid raft microdomains. The localization and adaptor functions recruit signaling proteins to discrete regions in the membrane and affect T cell signaling pathways [97]. Proteins associated with a survival and pro-angiogenic phenotype in severe PH such as PI-3 kinase, MAP kinases, and a p21 kinase-2 are all recruited to the rafts by Nef [98][99][100][101].…”
Section: Pathobiologymentioning
confidence: 99%
“…Phosphatidylcholine accounts to 75% of total phospholipid [85] GP Viral envelopes are enriched in sphingomyelin [8,86] SP Envelope cholesterol is critical for structure and infectivity [87][88][89] ST 2 Phosphatidylserine stimulates entry of enveloped viruses [90,91] Mannose receptor binds to the ManLAM mannose caps of mycobacteria and mediates phagocytosis [92] GPI anchored proteins (host [35,36] and parasite [37] …”
Section: Glmentioning
confidence: 99%